Spin catalytic material for promoting CO2 photo-reduction and preparation method thereof
By designing supramolecular metal grid catalytic materials and utilizing the spin state modification of the iron center, we have solved the problem of adjusting the electronic structure of multi-metal complexes in the existing technology, achieved efficient CO2 photoreduction reactions, and significantly improved the yield.
Patent Information
- Application Number
- CN202411468129.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The prior art has difficulty adjusting the metal-center electronic structure in polymetallic complexes, resulting in limited application of its high-performance catalyst in artificial photosynthesis.
A super -molecular metal grid catalytic material is designed, and the self -rotation state of the iron center is used for chemical modification through anti -yin ions to promote the CO2 light reduction reaction. This material is assembled by the pyrazine group to form a four -metal square super molecule, and iron atoms are used as oxidation reduction and spin -spin -crossing active centers.
By adjusting the ratio of spin states, the rate of the CO2 reduction reaction is significantly increased. Complex 2 exhibits a CO2 to CO yield twice as fast as complex 1 after 1 hour of illumination.
Smart Images

Figure CN119350398A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of carbon dioxide photoreduction catalytic materials and relates to a spin catalytic material for promoting CO2 photoreduction and a preparation method thereof. Background Art
[0002] As a common strategy in supramolecular chemistry, self-assembly provides an important "bottom-up" principle for obtaining artificial functional molecules from simple building blocks. Among the many synthetic strategies in the field of supramolecular chemistry, the coordination bond approach enables people to construct various multimetallic supramolecular structures, such as macrocycles, metal localizations, and metal grids, taking advantage of highly directional metal-ligand interactions. In fact, the modular nature of building blocks during self-assembly makes the synthesis of functional molecules much easier, and a huge library of nanoscale molecular structures has been established.
[0003] Although the implementation of supramolecular strategies has achieved breakthroughs in several disciplines, the prediction of the valuable properties required for the assembled systems is insufficient or impossible due to the difficulty in tuning the electronic structure of the metal centers. For example, in the field of artificial photosynthesis, modifying the electronic state by exploiting the local coordination environment around the catalytically active center has been demonstrated to be an effective method for efficient screening of high-performance catalysts. However, the effect of spin states on predictable activity and / or selectivity in supramolecular assemblies has long been overlooked, mainly because it is a formidable challenge to precisely control the local spin states of the catalytically active centers.
[0004] Intentionally combining many metal sites as accessible active components in multimetallic complexes endows attractive catalytic properties through high density of active sites and synergistic interactions among them. Some noble metal complexes, such as Ru(II), Pt(II), Ir(III), etc., have been widely used to construct photoactive metal-organic assemblies through some linear ligands. However, their lack of tunable electronic structures often prevents them from being used as suitable models to study the relationship between electronic structure and photocatalysis. Summary of the invention
[0005] The present invention provides a CO2 photoreduction-promoting spin catalytic material and a preparation method thereof, wherein the material is a supramolecular metal lattice in which the spin states of the iron centers can be chemically modified by counter anions to promote the photocatalytic CO2 reduction reaction (CO2RR). The pyrazine groups located in the middle position of the bridging ligand are expected to act as double-armed pockets to assemble tetrametallic square supramolecular. The supramolecular metal lattice uses iron atoms as redox and spin crossover active centers.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a catalytic material for promoting CO2 photoreduction spin, wherein the single crystal structure molecular formula of the material is: [Fe4(pbd)4]ClO4·CH3OH or Fe4(pbd)4·2CH3CN; wherein pbd is 2,2′-pyrazine dihydrazine methylthioamide. Its structural formula is shown in the following formula I;
[0008]
[0009] The materials are all tetragonal, with space groups of P4 / ncc. Their unit cell sizes are similar, with a and b being approximately c is α=90°, β=90°, γ=90°, Z=4.
[0010] Specifically, the unit cell parameters of the spin catalytic material having a single crystal structure formula of [Fe4(pbd)4]ClO4·CH3OH are α=90°, β=90°, γ=90°, Z=4,
[0011] The unit cell parameters of the spin catalytic material having a single crystal structure molecular formula of Fe4(pbd)4·2CH3CN are α=90°, β=90°, γ=90°, Z=4,
[0012] The second aspect of the present invention provides a method for preparing a spin catalytic material that promotes CO2 photoreduction, the method comprising:
[0013] S1. Preparation of organic ligand PBD: Add 2-acetylpyrazine to a double-necked round-bottom flask, place it in an ice bath, add anhydrous acetaldehyde and H2SO4, add tert-butyl peroxide dropwise, slowly add FeSO4 solution to the reaction flask through a constant pressure dropping funnel, remove the ice bath after the addition is complete, and stir at room temperature. After the reaction is completed, extract and distill under reduced pressure to obtain orange powder 2,5-diacetylpyrazine. Add 2,5-diacetylpyrazine and semicarbazide to anhydrous ethanol, add glacial acetic acid as a catalyst, heat to reflux and stir the reaction, then filter and dry to obtain a yellow powder product of 2,2′-pyrazinebishydrazine methylthioamide. The reaction formula for the synthesis of 2,2'-pyrazinebishydrazine methylthioamide from 2,5-diacetylpyrazine and semicarbazide is as follows:
[0014]
[0015] S2. Preparation of the complex [Fe4(pbd)4]ClO4·CH3OH: Add the ligand pbd into a single-necked flask containing methanol and heat to 70°C to obtain a yellow suspension. Add Fe(ClO4)2·xH2O to the suspension containing the ligand. The solution quickly turns black. Continue to reflux and stir for a period of time, then cool to room temperature. Filter and let stand in a beaker for slow evaporation. After one week, black square crystals are obtained.
[0016] S3. Preparation of complex Fe4(pbd)4·2CH3CN: Add the ligand pbd into a round-bottom flask containing methanol and heat to 70°C to obtain a yellow suspension. Dissolve Fe(CF3SO3)2 in acetonitrile and add it to the ligand suspension. The solution quickly turns black. Continue to reflux and stir for a period of time and then cool to room temperature. Filter the black solution and let it stand in a beaker to evaporate slowly. After one week, black square crystals are obtained.
[0017] Furthermore, in the step S1, the molar ratio of the 2,5-diacetylpyrazine to the semicarbazide is (9.9-10.1):(9.9-10.1), and the volume ratio of the ethanol to the glacial acetic acid is: (29.9 mL-30.1 mL):(0.3 mL-0.4 mL).
[0018] Furthermore, in the step S1, the stirring reaction time at room temperature is 5-6 hours.
[0019] Furthermore, in the step S1, the heating reflux stirring reaction time is 6-7h, and the temperature is 70°C to 80°C.
[0020] Furthermore, in the step S2, the molar ratio of the PBD and Fe(ClO4)2·xH2O is (0.2-0.4):(0.2-0.4); the usage ratio of the methanol and PBD is: (95 mL-105 mL):(0.2 mol-0.4) mol.
[0021] Furthermore, in the step S3: the molar ratio of the pbd and Fe(CF3SO3)2 is (0.2-0.4):(0.2-0.4), and the usage ratio of the pbd, methanol and acetonitrile is: (0.2mmol-0.4mmol):(25mL-35mL):(25mL-35mL).
[0022] Furthermore, in the steps S2 and S3, the reflux heating treatment time is 3 hours to 4 hours, and the reflux heating temperature is 65° C. to 75° C.
[0023] The third aspect of the present invention provides an application of a spin-catalyzed material for promoting CO2 photoreduction in the field of artificial photosynthesis as described above. The spin state of the iron center can be chemically modified by a counter anion to promote the photocatalytic CO2 reduction reaction (CO2RR). The pyrazine group located in the middle position of the bridging ligand is expected to be used as a double-arm pocket to assemble a four-metal square supramolecule. The supramolecular metal lattice uses iron atoms as redox and spin crossover active centers.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses 2,2'-pyrazine dihydrazine methylthioamide as a ligand, and synthesizes highly active metal grid supramolecular complexes 1 and 2 with Fe(ClO4)2·xH2O and Fe(CF3SO3)2 respectively by solvent evaporation method. Since complex 1 has a perchlorate ion participating in the crystallization, and each ligand exhibits 2 units of negative charge, the presence of Fe in the crystal molecule Ⅲ and Fe Ⅱ The average distance between two adjacent Fe ions is The dihedral angle between the two ligand faces is about 90°, and the average bond length of the axial Fe-N bond (N3, N7) is The average bond length of the Fe-N bond (N5, N4) is Longer than the axial key length The average bond length of Fe-S bonds on the warp plane is An axially compressed octahedral structure is formed.
[0026] The average distance between two adjacent Fe in complex 2 is The dihedral angle between the two ligands is about 90°, and the average bond length of the axial Fe-N bond (N3, N7) is The average bond length of the Fe-N bond (N5, N4) is Longer than the axial key length The average bond length of Fe-S bonds on the warp plane is An axially compressed octahedral structure is formed.
[0027] The complex provided by the present invention can be used as a photocatalyst to regulate multiple spin states on a single Fe site in a metal grid supramolecule to effectively promote the visible light-driven CO2 reduction reaction (CO2RR). Experimental studies and theoretical calculations show that Fe 3+ The single full spin state transition from low spin (LS, s = 1 / 2) to high spin (HS, s = 5 / 2) will inhibit the CO2RR activity, which will increase the Fe-3d of the photocatalyst and the O-2 pThe orbital overlap between them reduces the Gibbs free energy of forming the key intermediate. 2+ LS-Fe 3+ and HS-Fe 3+ ) complexes to improve the above problems.
[0028] The present invention also uses the counter anion to finely adjust the ratio of the spin state, further accelerating the CO2RR rate. Compared with complex 1, complex 2 only has about 10% more HS sites. Due to the partial spin transition of the active state, after 1 h of light irradiation, complex 2 (6.26 mmol g -1 ) showed a higher -1 ) twice as fast CO2 to CO yield, demonstrating an effective strategy to design spin-based photocatalysts via supramolecular assembly to promote artificial photosynthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 X-ray crystal structures of complex 1 (a) and complex 2 (b);
[0031] Figure 2 Infrared spectra of complex 1 (red line) and complex 2 (black line);
[0032] Figure 3 Powder X-ray diffraction patterns of complex 1 (a) and complex 2 (b);
[0033] Figure 4 The photocatalytic gas production of complex 1 (a) and complex 2 (b) changes with time;
[0034] Figure 5 Cyclic voltammetry curves of complex 1 (a) and complex 2 (b) under different atmospheres;
[0035] Figure 6 It is the electron transfer pathway for the photocatalytic reduction of CO2 in the catalytic system of the present invention;
[0036] Figure 7 This is the spin conversion mode in the photocatalytic reaction of the present invention. DETAILED DESCRIPTION
[0037] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a preparation method of a CO2 photoreduction spin catalytic material proposed by the present invention, its specific implementation method, characteristics and effects are described in detail as follows. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] The reagents involved in the experiment were from manufacturers such as Anage Chemical and Shanghai Lingfeng, and the details are shown in Table 1; the reagents involved were used directly without further purification.
[0039] Table 1 Reagents
[0040]
[0041]
[0042] The equipment and instruments used in the experiment are shown in Table 2:
[0043] Table 2 Main instruments
[0044]
[0045] Example 1
[0046] Preparation of ligand PBD: 2-acetylpyrazine (3.05 g, 25 mmol) was added to a double-necked round-bottom flask, placed in an ice bath, and 5.8 mL of anhydrous acetaldehyde and 6.2 mL of 3.4 mol·L -1 of H2SO4, add 6.0 mL of tert-butyl peroxide, and use a constant pressure dropping funnel to add 54 mL of 1.6 mol L -1 The FeSO4 solution was slowly added to the reaction flask, and the ice bath pot was removed after the addition was completed. The mixture was stirred at room temperature for 5 hours. After the reaction was completed, the mixture was extracted and distilled under reduced pressure to obtain orange powder 2,5-diacetylpyrazine. 2,5-diacetylpyrazine (1.64 g, 10 mmol) and semicarbazide (0.91 g, 10 mmol) were added to 30 mL of anhydrous ethanol, and 3 drops of glacial acetic acid were added as a catalyst. The mixture was heated at 70°C and refluxed for 6 hours, and then filtered and dried to obtain a yellow powder product of 2,2'-pyrazine dihydrazine methylthioamide.
[0047] Preparation of complex 1 [Fe4(pbd)4]ClO4·CH3OH: The ligand pbd (0.0620 g, 0.2 mmol) synthesized above was added into a single-necked flask with 90 mL of methanol and heated to 70°C to obtain a yellow turbid liquid. Fe(ClO4)2·xH2O (0.0509 g, 0.2 mmol) was added into 10 mL of methanol to dissolve and then added into the ligand suspension. The solution quickly turned black. After continuing to reflux and stir for 3 hours, it was cooled to room temperature, filtered and allowed to stand in a beaker for slow evaporation. After one week, black square crystals were obtained.
[0048] Preparation of complex 2Fe4(pbd)4·2CH3CN: Add the ligand pbd (0.0620 g, 0.2 mmol) into a round-bottom flask with 30 mL of methanol and heat to 70°C to obtain a yellow turbid liquid. Add Fe(CF3SO3)2 (0.7079 g, 0.2 mmol) into 30 mL of acetonitrile to dissolve it and then add it to the ligand suspension. The solution quickly turns black. Continue stirring for 3 hours and then cool to room temperature. Filter the black solution and let it stand in a beaker to evaporate slowly. After a week, black square crystals are obtained.
[0049] The crystallographic data of complexes 1 and 2 were obtained on a Bruker APEX-IICCD instrument equipped with graphene monochromatic radiation. Collected at the corresponding temperature. Use Bruker Instrument Servicev4.2.2 and SAINTV8.34A two program packages for data collection, data reduction and unit optimization. Use SHELXS program package to analyze the structure of the complex, and use the full matrix least squares method to optimize the crystal data through the SHELXL program package. Use the multi-scan program package SADABS for absorption correction. The hydrogen atoms of the organic ligands are anisotropically optimized on F2 through the riding mode on the SHELXTL program package. The crystallographic data of the complex are shown in Table 3.
[0050] Table 3 Crystallographic parameters of the complexes
[0051]
[0052]
[0053] a R1=Σ(||F0|-|Fc||) / Σ|F0|; b wR2=[Σw(|F0 2 |-|Fc 2 |) 2 / Σw|F0 2 | 2 ] 1 / 2 ; cGOF=[∑[w(F0 2 -Fc 2 ) 2 ] / (Nobs-Nparams)] 1 / 2 , based on the data I>2σ(I).
[0054] Complex 1 is a tetragonal system with a space group of P4 / ncc. The unit cell parameters of the complex are α=90°, β=90°, γ=90°, Z=4, Since there is a perchlorate ion involved in the crystallization, and each ligand exhibits 2 units of negative charge, the presence of Fe in the crystal molecule Ⅲ and Fe Ⅱ The average distance between two adjacent Fe ions is The dihedral angle between the two ligand faces is about 90°, and the average bond length of the axial Fe-N bond (N3, N7) is The average bond length of the Fe-N bond (N5, N4) is Longer than the axial key length The average bond length of Fe-S bonds on the warp plane is An axially compressed octahedral structure is formed.
[0055] The single crystal structure of complex 2 is Fe4(pbd)4·2CH3CN, where pbd is 2,2'-pyrazine dihydrazine methylthioamide. In the material, complex 2 is a tetragonal system with a space group of P4 / ncc. The unit cell parameters of the complex are α=90°, β=90°, γ=90°, Z=4, The average distance between two adjacent Fe is The dihedral angle between the two ligands is about 90°, and the average bond length of the axial Fe-N bond (N3, N7) is The average bond length of the Fe-N bond (N5, N4) is Longer than the axial key length The average bond length of Fe-S bonds on the warp plane is An axially compressed octahedral structure is formed.
[0056] Infrared absorption spectroscopy analysis: Figure 2 As shown, the red line is the infrared spectrum of complex 1, and complex 1 has a wavelength of 1100 cm -1 The peak with medium intensity is the crystalline anion ClO4 - The absorption peak of complex 2 is 1600 cm-1 The peak at is the stretching vibration peak of the Schiff base C=N bond on the ligand.
[0057] Powder X-ray diffraction analysis: Figure 3 As shown, Figure 3 As shown in (a), the red spectrum is the powder diffraction test data of the complex 1 crystal, and the black spectrum is the data simulated by the software. It can be seen that the experimental value and the simulated value of complex 1 are in good agreement, indicating that the complex is pure; Figure 3 As shown in (b), the red spectrum is the powder diffraction test data of complex 2, and the black spectrum is the data simulated by the software. It can be seen that the experimental value and the simulated value of complex 2 are in good agreement, indicating that the complex is pure.
[0058] Analysis of catalytic performance of complex 1 and complex 2: Complex 1 or complex 2 was added as catalyst (1 mg) in a photocatalytic reaction vessel, the photosensitizer was tri(2,2'-bipyridyl)ruthenium(II) chloride hexahydrate (1 mg), the sacrificial agent was 1,3-dimethyl-2-phenylbenzimidazolidine (14 mg), and the solvent system was acetonitrile: water = 4.8:0.2. CO2 was introduced into the photocatalytic system for 15 min, and the light intensity was 100 mW cm -2 The samples were irradiated for 5 h and then detected by gas chromatography.
[0059] Analysis of gas production over time: Figure 4 As shown, gaseous products such as CO and H2 were analyzed by gas chromatography. Liquid products were detected by ion chromatography, but only trace amounts of HCOOH were detected. For the CO2 reduction reaction, as the illumination time increased, both complexes 1 and 2 tended to stabilize at 3 h. With complex 1 as the photocatalyst, the CO yield reached 2.96 mmol g after 1 hour of initial light irradiation. -1 However, when complex 2 was used as the catalyst, the CO yield reached 6.26 mmol g -1 , which is more than twice that of complex 1.
[0060] Cyclic voltammetry curve analysis: Figure 5 As shown, in order to further reveal the electron transfer between the photocatalyst and CO2 reduction, cyclic voltammetry (CV) tests of the photocatalyst were carried out in N2 and CO2 atmospheres, respectively. In N2 atmosphere, the CV of complexes 1 and 2 showed three irreversible reduction waves. For complex 1, the Fe 3+ / 2+ , -0.21VFe 2+ / 1+ and -0.31V Fe 1+ / 0 ; for complex 2, Fe is 0.42V 3+ / 2+ , -0.35VFe 2+ / 1+and -0.58V Fe 1+ / 0 The reduction current of complex 1 in CO2 atmosphere is slightly lower than that in N2 atmosphere, indicating that the electron transfer activity of complex 1 to CO2 is poor. +1 / 0 After the redox event, the current intensity of complex 2 in CO2 atmosphere suddenly increased, and Fe 2+ / 1 + and Fe 1+ / 0 The redox potential of the photocatalyst 2 showed a significant positive shift, indicating that complex 2 was more active in catalyzing the reduction of CO2. Therefore, from the experimental observation of the CV curve, complex 2 has a stronger electron transfer activity for CO2 reduction as a photocatalyst than complex 1.
[0061] Electron transfer pathway analysis: Figure 6 As shown in Figure 3, the quenching mode of activated RuPS* can be classified as an oxidative quenching pathway. The photocatalytic CO2RR is initiated by the electron transfer from the photoexcited RuPS* to the photocatalyst, which produces reduced Fe, thereby injecting electrons into the CO2RR.
[0062] Analysis of spin transition patterns in photoreduction reactions: Figure 7 As shown in the figure, the active Fe sites of complexes 1 and 2 adopt an unprecedented three-component mixed spin state (i.e., HS-Fe 2+ LS-Fe 3+ and HS-Fe 3+ ), where the ratio of spin states can be finely tuned by the counter anion. Therefore, the mixed spin metal grid provides an ideal model to clarify the spin state effect of the active center after photocatalysis. Compared with complex 1, complex 2 only undergoes a subtle spin transition of about 10% of the Fe sites, which greatly improves the CO2RR rate. 3+ The Fe metal grid with (HS, s = 5 / 2) sites (complex 2) has a higher CO2RR rate than the Fe metal grid with more low-spin sites. 3+ The iron metal grid (complex 1) at the (LS, s = 1 / 2) site is twice as large.
[0063] Example 2
[0064] Preparation of ligand PBD: 2-acetylpyrazine (3.05 g, 25 mmol) was added to a double-necked round-bottom flask, placed in an ice bath, and 5.8 mL of anhydrous acetaldehyde and 6.2 mL of 3.4 mol·L -1 of H2SO4, add 6.0 mL of tert-butyl peroxide, and use a constant pressure dropping funnel to add 54 mL of 1.6 mol L -1The FeSO4 solution was slowly added to the reaction flask, and the ice bath pot was removed after the addition was completed. The mixture was stirred at room temperature for 5 hours. After the reaction was completed, the mixture was extracted and distilled under reduced pressure to obtain orange powder 2,5-diacetylpyrazine. 2,5-diacetylpyrazine (1.64 g, 10 mmol) and semicarbazide (0.91 g, 10 mmol) were added to 30 mL of anhydrous ethanol, and 3 drops of glacial acetic acid were added as a catalyst. The mixture was heated at 70°C and refluxed for 6 hours, and then filtered and dried to obtain a yellow powder product of 2,2'-pyrazine dihydrazine methylthioamide.
[0065] Preparation of complex (1) [Fe4(pbd)4]ClO4·CH3OH: The ligand pbd (0.0930 g, 0.3 mmol) synthesized above was added into a single-necked flask containing 90 mL of methanol and heated to 70°C to obtain a yellow turbid liquid. Fe(ClO4)2·xH2O (0.0762 g, 0.3 mmol) was added into 10 mL of methanol to dissolve and then added into the ligand suspension. The solution quickly turned black. After continuing to reflux and stir for 3 h, it was cooled to room temperature, filtered and allowed to stand in a beaker for slow evaporation. After one week, black square crystals were obtained.
[0066] Preparation of complex (2) Fe4(pbd)4·2CH3CN: Add the ligand pbd (0.0930 g, 0.3 mmol) into a round-bottom flask with 30 mL of methanol and heat to 70°C to obtain a yellow turbid solution. Add Fe(CF3SO3)2 (0.1062 g, 0.3 mmol) into 30 mL of acetonitrile to dissolve it and then add it to the ligand suspension. The solution quickly turns black. Continue stirring for 3 hours and then cool to room temperature. Filter the black solution and let it stand in a beaker to evaporate slowly. After one week, black square crystals are obtained.
[0067] Example 3
[0068] Preparation of ligand PBD: 2-acetylpyrazine (3.05 g, 25 mmol) was added to a double-necked round-bottom flask, placed in an ice bath, and 5.8 mL of anhydrous acetaldehyde and 6.2 mL of 3.4 mol·L -1 of H2SO4, add 6.0 mL of tert-butyl peroxide, and use a constant pressure dropping funnel to add 54 mL of 1.6 mol L -1 The FeSO4 solution was slowly added to the reaction flask, and the ice bath pot was removed after the addition was completed. The mixture was stirred at room temperature for 5 hours. After the reaction was completed, the mixture was extracted and distilled under reduced pressure to obtain orange powder 2,5-diacetylpyrazine. 2,5-diacetylpyrazine (1.64 g, 10 mmol) and semicarbazide (0.91 g, 10 mmol) were added to 30 mL of anhydrous ethanol, and 3 drops of glacial acetic acid were added as a catalyst. The mixture was heated at 70°C and refluxed for 6 hours, and then filtered and dried to obtain a yellow powder product of 2,2'-pyrazine dihydrazine methylthioamide.
[0069] Preparation of complex (1) [Fe4(pbd)4]ClO4·CH3OH: The ligand pbd (0.1240 g, 0.4 mmol) synthesized above was added into a single-necked flask containing 95 mL of methanol and heated to 70°C to obtain a yellow turbid liquid. Fe(ClO4)2·xH2O (0.1019 g, 0.4 mmol) was added into 10 mL of methanol to dissolve and then added into the ligand suspension. The solution quickly turned black. After continuing to reflux and stir for 3 h, it was cooled to room temperature, filtered and allowed to stand in a beaker for slow evaporation. After one week, black square crystals were obtained.
[0070] Preparation of complex (2) Fe4(pbd)4·2CH3CN: Add the ligand pbd (0.1240 g, 0.4 mmol) into a round-bottom flask with 35 mL of methanol and heat to 70°C to obtain a yellow turbid liquid. Add Fe(CF3SO3)2 (0.1415 g, 0.4 mmol) into 35 mL of acetonitrile to dissolve it and then add it to the ligand suspension. The solution quickly turns black. Continue stirring for 3 hours and then cool to room temperature. Filter the black solution and let it stand in a beaker to evaporate slowly. After a week, black square crystals are obtained.
[0071] In Examples 2 and 3, the concentration of reactants was increased, which made it easier to form a precipitate, but the obtained crystals had poor rigidity and weak diffraction.
[0072] This work reports that multiple spin states on a single Fe site in a metal lattice supramolecule can effectively promote the visible light-driven CO2 reduction reaction (CO2RR). Experimental studies and theoretical calculations show that the CO2RR activity is driven by Fe 3+ The complex of the present invention is triggered by the spin state transition from low spin (LS, s = 1 / 2) to high spin (HS, s = 5 / 2), which increases the orbital overlap between the Fe-3d of the photocatalyst and the O-2p of the CO2 substrate, thereby reducing the Gibbs free energy of the key intermediate formation. 2+ LS-Fe 3+ and HS-Fe 3+ ) to improve the above problems. The present invention further adjusts the ratio of the spin state of the complex by counter anions. Due to the partial spin transition of the active lattice, after 1 hour of illumination, the CO2 to CO yield of the supramolecular metal lattice containing only about 10% HS sites is reduced to 6.26mmol g -1 ) than LS lattice (2.96mmol g -1 ) twice as fast. This work demonstrates an effective strategy to design spin-based photocatalysts via supramolecular assembly to promote artificial photosynthesis.
[0073] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A spin catalytic material for promoting CO2 photoreduction, characterized in that: The single crystal structure molecular formula of the spin catalytic material is: [Fe4(pbd)4]ClO4·CH3OH or Fe4(pbd)4·2CH3CN, wherein pbd is 2,2'-pyrazine dihydrazine methylthioamide, and its structural formula is shown in the following formula I; 2. The CO2 photoreduction promoting spin catalytic material according to claim 1, characterized in that: The spin catalytic material with the single crystal structure formula of [Fe4(pbd)4]ClO4·CH3OH is a tetragonal crystal system with a space group of P4 / ncc and a unit cell parameter of α=90°, β=90°, γ=90°, Z=4, 3. The CO2 photoreduction promoting spin catalytic material according to claim 1, characterized in that: The spin catalytic material with the single crystal structure formula of Fe4(pbd)4·2CH3CN is a tetragonal crystal system with a space group of P4 / ncc and a unit cell parameter of α=90°, β=90°, γ=90°, Z=4, 4. A method for preparing a CO2 photoreduction promoting spin catalytic material according to any one of claims 1 to 3, characterized in that: The steps include: S1. Preparation of organic ligand PBD: 2,5-diacetylpyrazine and thiosemicarbazide are added to anhydrous ethanol, glacial acetic acid is added as a catalyst, and the mixture is heated to reflux and stirred for reaction, and then filtered and dried to obtain a yellow powder product of 2,2'-pyrazine dihydrazine methylthioamide; the 2,5-diacetylpyrazine is shown in the following formula II: S2. Preparation of a spin catalytic material with a single crystal structure and a molecular formula of [Fe4(pbd)4]ClO4·CH3OH: Add the ligand pbd to a single-necked flask containing methanol and heat to 70°C to obtain a yellow suspension, add Fe(ClO4)2·xH2O to the suspension containing the ligand, the solution quickly turns black, continues to reflux and heat, then cools to room temperature, filters and places in a beaker to slowly evaporate, and obtains black square crystals; S3. Prepare a spin catalytic material with a single crystal structure and the molecular formula is Fe4(pbd)4·2CH3CN: add the ligand pbd into a round-bottom flask containing methanol and heat it to 70°C to obtain a yellow suspension. Add Fe(CF3SO3)2 into acetonitrile to dissolve it and then add it to the ligand suspension. The solution quickly turns black. After reflux heating, cool to room temperature. Filter the black solution and let it stand in a beaker to slowly evaporate to obtain black square crystals.
5. The method for preparing a spin-catalyzing material for promoting CO2 photoreduction according to claim 4, characterized in that: In the step S1, the molar ratio of the 2,5-acetylpyrazine to the semicarbazide is (9.9-10.1):(9.9-10.1), and the volume ratio of the ethanol to the glacial acetic acid is: (29.9 mL-30.1 mL):(0.3 mL-0.4 mL).
6. The method for preparing a spin-catalyzing material for promoting CO2 photoreduction according to claim 4, characterized in that: In the step S1, the heating reflux stirring reaction time is 6-7h, and the temperature is 70°C to 80°C.
7. The method for preparing a spin-catalyzing material for promoting CO2 photoreduction according to claim 4, characterized in that: In the step S2, the molar ratio of the PBD and Fe(ClO4)2·xH2O is (0.2-0.4):(0.2-0.4); the usage ratio of the methanol and PBD is: (95 mL-105 mL):(0.2 mmol-0.4 mmol).
8. The method for preparing a spin-catalyzing material for promoting CO2 photoreduction according to claim 4, characterized in that: In the step S3: the molar ratio of the PBD and Fe(CF3SO3)2 is (0.2-0.4):(0.2-0.4), and the usage ratio of the PBD, methanol and acetonitrile is: (0.2mmol-0.4mmol):(25mL-35mL):(25mL-35mL).
9. The method for preparing a spin-catalyzing material for promoting CO2 photoreduction according to claim 4, characterized in that: In the steps S2 and S3, the reflux heating treatment is performed for 3 hours to 4 hours at a temperature of 65° C. to 75° C.
10. Use of the spin catalytic material for promoting CO2 photoreduction as claimed in any one of claims 1 to 3 in the field of artificial photosynthesis.
Citation Information
Patent Citations
Catalytic material for efficiently photo-reducing carbon dioxide as well as preparation method and application of catalytic material
CN117447528A
Metal-ligand catalysts for selective promotion of electrochemical co2rr
US20210238212A1